2012
DOI: 10.1258/ijsa.2012.012040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of timing of antiretroviral therapy initiation on survival of cervical squamous intraepithelial lesions: a cohort analysis from South Africa

Abstract: To determine factors that influence excision treatment outcome and recurrence of cervical squamous intraepithelial lesions (SIL) in women living with HIV infection, we analysed 1848 women who underwent excision treatment of cervical SIL at Tygerberg Hospital, Cape Town, South Africa. We compared treatment failure defined as presence of cervical intraepithelial neoplasia (CIN) I (presence of CIN I or higher at first follow-up after excision treatment) and post-excision recurrence of lesions (at one year or late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Persistence and recurrence of CIN2 + after treatment is more common among WLWH and the most important risk factor seems to be a low CD4 + T‐cell count . ART is associated with reduction of the incidence and progression of cervical dysplasia among WLWH, further stressing the importance of identifying women with cervical dysplasia who are unaware of their HIV status …”
Section: Discussionmentioning
confidence: 67%
“…Persistence and recurrence of CIN2 + after treatment is more common among WLWH and the most important risk factor seems to be a low CD4 + T‐cell count . ART is associated with reduction of the incidence and progression of cervical dysplasia among WLWH, further stressing the importance of identifying women with cervical dysplasia who are unaware of their HIV status …”
Section: Discussionmentioning
confidence: 67%
“…Additionally, several studies have not adjusted for CD4 nadir, current CD4 count, or time on ART, which may explain why the association between ART and progression/regression of cervical lesion has remained uncertain for so long 107,108 . There are studies, however, adjusting for CD4 count and time on ART that have shown an association between ART and outcome of CIN and recently a meta-analysis confirmed reduced incidence of HSIL/CIN2+, decreased progression of SIL, increased SIL/CIN regression and reduced incidence of ICC among women on ART 78,103,[109][110][111] .…”
Section: Icc and Cin In Women Living With Hivmentioning
confidence: 99%
“…Persistence and recurrence of CIN2/3 after treatment with conization is more common in WLWH and increases with the level of immunosuppression 104,110,113,114 . It is unclear if WLWH on ART have better outcome after conization than those not on ART as data is limited.…”
Section: Treatment Of Icc/cin In Women Living With Hivmentioning
confidence: 99%
“…9,10 Although access to highly active antiretroviral therapy (HAART) in many countries has dramatically increased over the past decade, the impact of HAART on the development of cervical precancer and recurrence after treatment remain unclear. 1115 This means that an increasing number of HIV-infected women are living longer with a potentially higher risk for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%